Historical blocking: KZ 2022-01-04 (Kazakhstan) - Voidly (Voidly Global Censorship Index, 2022)
WARNING severity censorship detected in Kazakhstan. Data sourced from ooni-historical-backfill.
Censorship Incident ID: KZ-2022-0009. Severity: warning. Confidence: 77%